A taxonomic evaluation of the Thesium confine species complex (Santalaceae) - Kagiso S. Mashego; M. Marianne le Roux (Bothalia: African Biodiversity & Conservation, 2018)
Background: Thesium L. is the largest genus in the family Santalaceae (sandalwood family). The last taxonomic revision of the southern African species dates back to 1925. An urgent revision of the genus is required as indicated in a recent national biosystematics research strategy for South Africa.